Review paperIntermediate coronary artery stenosis – when is intervention indicated and when should it be deferred? Value of intravascular ultrasound in clinical decision making in the performance of coronary interventions - Radomski, Marek; Rychter, Marcin; Sukiennik, Adam; Kubica, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2006)
intravascular ultrasound, coronary artery disease, intermediate stenosis